PENGGUNAAN MEDIA BELAJAR PAROREB UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA MATERI ROTASI DAN REVOLUSI BUMI KELAS VI SD: Penelitian Tindakan Kelas - Is Dinawati Purba; Asrar Aspia Manurung; Anhar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve sixth-grade students’ conceptual understanding of Earth's rotation and revolution through the use of a concrete learning media called the Earth Rotation and Revolution Board (PAROREB). The research was conducted using Classroom Action Research (CAR) in two cycles, each consisting of planning, action, observation, and reflection. The results showed a significant improvement in students’ understanding. The average pre-test score of 53.57 increased to 68.21 in the first cycle and 82.50 in the second. The percentage of students achieving the Minimum Mastery Criteria (KKM) rose from 35.7% in the pre-cycle to 42.85% in cycle I and reached 85% in cycle II. PAROREB proved effective not only in enhancing learning outcomes but also in fostering active participation and student confidence during the learning process. Thus, this media can serve as a relevant and efficient alternative for teaching natural science topics in elementary school, particularly Earth’s rotation and revolution.